The Circle of Innovation: You Can’t Shrink Your Way to Greatness Book Review - Arooj Zeb; Dr. Anjum Ihsan (Journal of Business & Tourism, 2021)
The book “Circles of Innovation” is written by Tom Peters who is called as the father of branding and a business guru. In this book Tom Peters has given us 15 discrete ideas that logically, systematically and coherently add up to the “one big idea” i.e. Innovation. Through 400 seminars in 47 states and 22 countries in five years, Peters has refined and reinvented his views on innovation. The whole idea of this book is either to be innovative or die. This book is a blend of thoughts, quotes and exclamation points which are very inspiring and thought provoking for the readers. Practical examples of successful businesses have been given which focus on innovation. This book is very inspiring as it has got blog graphics, facts and figures that sources range from Martha Steward to Bill Gates. This book is very helpful for those who want to know about how to bring innovation in the organization. The Circle of Innovation is for all those who run a business of any size; from a six-person department to a large business having 500 plus employees, it empowers the readers to transform their organizations by following the useful tips of innovation mentioned in this book. "No matter where you are in your career, this book is a must read. The younger your thinking, the more you’ll get out of it."